Critical Reviews on the Methodology in Law: A Case Study of Introduction to Research Methods in Law - Mohammad Saeed Taslimi; Khalil Norouzi; Mohammad Amin Hakemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Methodology is important in every science. Legal studies, for a long time, has been in the deficiency of suitable methodology and methods of doing research. In spite of this specific deficiency, in other fields of human sciences, such as management, there exist some advancements that can solve many issues in legal studies. Because of the absence of modern research methods in legal studies, it has been a long time that we have seen an obvious downtrend in this field. In spite of this unacceptable practice in law science, we see impressive movements and advancements in management science. Therefore, this paper by analyzing the book “ Method of Research in Legal Studies”, written by Dr. Javid tries to make these two fields, law and management, closer, hoping that in the future, the rapprochement  of these two fields can solve the issues of society by applying new methods of management sciences to law sciences.